"School definitely failed me, the system failed me": Identifying opportunities to impact educational outcomes for homeless and child welfare-involved youth. (August 2018) - Semanchin Jones, Annette; Bowen, Elizabeth; Ball, Annahita
Abstract: Children and youth who experience homelessness and child welfare involvement may experience high mobility, disruption of relationships with family and peer networks, and social stigma, all of which can have a negative impact on educational success for these youth. In this study, we explored the perspective of youth who were involved with child welfare and homeless serving systems, and who had experienced school challenges. Youth ( n = 20) between the ages of 18 and 24 participated in semi-structured qualitative interviews. Using a life course framework, we asked youth about their experiences in these multiple systems across developmental stages, and asked them to highlight what might have been helpful to their educational outcomes. Data analysis was conducted by a research team of three scholars who each had expertise in these varied systems, and member checking was completed with four youth to increase credibility of the findings. Results highlighted the importance of youth having supportive adults in their lives, suggesting an opportunity for systems to better mobilize and support caring adults, including informal supports and professional staff within these systems that can advocate for youth. Results also stress the importance of using a trauma-informed approach with cross- systems youth, rather than punitive approaches to discipline that tend to exacerbate negative educational outcomes. Many of these youth felt like they had to "make it on their own, " underscoring the need to better connect youth to existing resources within their communities and building on youths' strengths and protective factors, in order to improve educational outcomes for vulnerable youth. Highlights: Qualitative study with cross-system youth on their experiences in child welfare, homeless-serving, and education systems. Youth highlighted potential points of intervention to improve educational outcomes. Results indicate the importance of mobilizing and supporting informal mentors to better advocate for vulnerable youth. Youth stressed the importance of understanding negative behaviors in context, using a trauma-informed approach.